PENGARUH LATIHAN ABC RUNNING TERHADAP POWER TUNGKAI PESERTA DIDIK EKSTRAKURIKULER BOLA VOLI - Wardianto, Wardianto; Simanjuntak, Victor; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe  problem in this study is whether Acceleration  Balance Coordination (ABC) Running  affects  the  power of  leg muscles  of  students  in  extracurricular  MAN  1  Pontianak.  The  purpose  of  this  study  was to  determine  the  effect  of ABC  training  running  on  the  strength of  leg  muscle  power  in  jumping  smash  of extracurricular volleyball game MAN 1 Pontianak The population in this study were 12 people. By taking samples using saturated sample techniques, the number of samples is 12 people. The method used is an experiment with pre-experimental design. Data analysis techniques use the t-test formula. Based on the results of this t-test, obtained t count itung (>) t table, namely the value of t count 1.52 and t table 2.89 with a significant rate of 5%. Then Ho is refused and Ha is accepted. This means that there is an influence on the 12.44% running ABC coordination (ABC) running, on the extracurricular leg muscle power of MAN 1 Pontianak.Keywords: Exercise, ABC running, Power, Volleyball.